MODEL INTERAKSI STAKEHOLDER PADA PEMBEBASAN LAHAN PEMBANGUNAN JALAN TOL RUAS PADANG – SICINCIN - Helny Lalan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Toll roads are an effective means of transportation to shorten the distance between regions. With a short distance, the cost of accommodation of goods will decrease and increase accessibility, thereby encouraging economic improvement and community development. One of the toll roads currently under construction in West Sumatra is the Padang-Pekanbaru toll road. The Padang-Sicincin section is part of the large project with a length of 30.4 km. Since being carried out in 2018 the progress of the work has only reached 45.2%, meaning that there are obstacles that slow down the completion of the work. From the literature study, it was found that the main cause of delay was land acquisition. The various literatures also describe the resolution of disputes involving stakeholders. Stakeholder management is one of the indicators of project success. To find out the model of stakeholder interaction on the Padang-Sicincin spatial toll road project in terms of land acquisition, a social network analysis was carried out based on a literature study related to land acquisition, followed by the creation of a stakeholder relationship matrix. From the results of the analysis, it is found that stakeholders as the main actors in land acquisition are local governments as mediators and messengers between land owners and other stakeholders involved in land acquisition.Keywords: Stakeholders, Land Acquisition, Toll Roads, Social Network Analysis.